Investment outlook for the very large crude carrier (VLCC) segment from 2019 to 2023 - Tan, Terry De Jian (2018)
This research investigates the freight market outlook for the VLCC tanker segment from 2019 to 2023 and recommends whether investors should venture into this shipping market segment. Firstly, the investment potential of the VLCC tanker segment is investigated as an equity based on historical market risk and return. This is done by comparing with the industry actual and required rate of return against S&P 500 using the CAPM model. The generated results suggest that the tanker shipping business with its high financial and operating leverage is perceived as highly risk-laden investment. Additionally, the average Return on Equity (ROE) of VLCC operating companies is also lower than the average shipping industry that has similar risk profile. Next, the paper investigates relevant variables of the freight model and the influence on freight rates. The research produced direct demand variables and supply variables. By analysing the relationship of these variables, the impact of these factors on the freight market is derived and forecast to be between USD18, 500 to USD23,000/day for the next five years. It can be concluded that the VLCC market will be going through slow growth rates from 2019 to 2023 and thus will have little realistic chances for investing. The economic feasibility of investing into the VLCC segment will now be evaluated in different scenarios: buy new ships, buy second-hand ships and time-charter in ships. This will be done in volume II of the paper.